Beyond self-tracking: Exploring and unpacking four emerging labels of patient data work. (September 2019) - Piras, Enrico Maria
Despite the growing attention of researchers, healthcare managers and policy makers, data gathering and information management practices are largely untheorized areas. In this work are presented and discussed some early-stage conceptualizations: patient-generated health data, observations of daily living, quantified self and personal health information management. As I shall try to demonstrate, these labels are not neutral; rather, they underpin quite different perspectives with respect to health, patient–doctor relationship and the status of data.